2014
DOI: 10.1016/j.jphys.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic capacity and upper limb strength are reduced in women diagnosed with breast cancer: a systematic review

Abstract: Aerobic capacity and upper extremity strength in women diagnosed with breast cancer are generally lower than population norms. Assessment of values for lower extremity strength is less conclusive. As more research is published, expected values for sub-groups by age, treatment, and co-morbidities should be developed. [Neil-Sztramko SE, Kirkham AA, Hung SH, Niksirat N, Nishikawa K Campbell KL (2014) Aerobic capacity and upper limb strength are reduced in women diagnosed with breast cancer: a systematic review.Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 38 publications
4
52
0
6
Order By: Relevance
“…The positive effects generated by the meta-analyses for a range of inflammatory mediators justify investigation into the mechanisms underlying these effects so that exercise training exercise can be more precisely prescribed to optimize the prognosis of people with breast cancer. In the interim, exercise training can be encouraged in people during or after breast cancer treatment: because of its known benefits on the problems that cancer induces in physical fitness, function, fatigue, depression, and quality of life (23,24,32,34,35,(48)(49)(50)(51); because of the favorable trends observed in survival with exercise training (38,39); and now also, given the results of this review, because of its positive effects on inflammatory mediators in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects generated by the meta-analyses for a range of inflammatory mediators justify investigation into the mechanisms underlying these effects so that exercise training exercise can be more precisely prescribed to optimize the prognosis of people with breast cancer. In the interim, exercise training can be encouraged in people during or after breast cancer treatment: because of its known benefits on the problems that cancer induces in physical fitness, function, fatigue, depression, and quality of life (23,24,32,34,35,(48)(49)(50)(51); because of the favorable trends observed in survival with exercise training (38,39); and now also, given the results of this review, because of its positive effects on inflammatory mediators in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there still is insufficient information available to define the physiological mechanism for any potential benefit of exercise in reducing fatigue during cancer therapy or decreasing cancer risk. [43][44][45][46][47][48] In contrast to other systematic reviews in this area, the trials included in the present review all analysed participants during an active treatment stage -the most frequent treatment was chemotherapy (n = 1028). Oechsle et al, 49 in a recent prospective randomised pilot trial, found that supervised exercise improved fatigue among 48 participants receiving myeloablative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It manifests as a chronic edema, causing discomfort, loss of function, deformity and fatigue 3,4 . Psychological changes are also observed and negatively affect body image and self-esteem 5 . According to the International Society of Lymphology 6,7 , lymphedema can be classified into three degrees.…”
Section: Introductionmentioning
confidence: 99%